Initial performance of ten oil palm cross combinations under three agro-climatic conditions in India - G. Reddi, Sanjeevraddi; Gawankar, M.S.; Maheswarappa, H.P.; Latha, P. Madhavi Latha; Mathur, R.K. (Journal of Plantation Crops, 2017)
High yielding hybrids can play an important role in increasing the productivity of oil in the oil palm. With a view to evaluate high yielding new oil palm cross combinations, a field experiment was conducted in different agro-climatic regions of India viz., Zone No-10 Southern Plateau and Hills (Gangavathi, Karnataka), Zone No-12 Western Coastal Plains and Ghats (Mulde, Maharashtra) and Zone No-11 Eastern Coastal Plains and Hills (Vijayarai, Andhra Pradesh) involving ten cross combinations of tenera oil palm (NRCOP 1-10). The data from three locations over two years indicated that, significantly higher annual rate of leaf production per palm was recorded in NRCOP-6 (21.7) compared to NRCOP-3 and it was on par with other hybrid combinations. Significantly higher sex ratio was recorded with NRCOP-4 (63.1%) compared to NRCOP-1 (54.6%) and NRCOP-6 (54.8%) and was on par with other hybrid combinations.The hybrid cross combination, NRCOP-4 recorded significantly higher fresh fruit bunches (FFBs) yield 12.5 t ha-1 compared to NRCOP-1, NRCOP-3, NRCOP-7 and NRCOP-9 and it was on par with remaining hybrids and a similar result in bunch weight and number of bunches per palm was recorded. Pooled data on FFB yield for 2013-15 indicated that the hybrid combination NRCOP-4 which recorded higher FFB yield (12.6 t ha-1) at Gangavathi and at Vijayarai (22.6 t ha-1) have better prospects for adaptation under Tungabhadra command area and coastal region of Andhra Pradesh. For Konkan region of Maharashtra, the hybrid NRCOP-8 recorded the highest FFB yield.